2013
DOI: 10.1039/c2cp42649h
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation dynamics of laser ablation of bulk and wire-shaped metals in water during nanoparticles production

Abstract: Although the first nanoseconds to microseconds rule the resulting process yield of laser ablation in liquid, a comprehensive view involving combination of time-resolved measurement techniques is still lacking. In this paper, fundamental aspects of laser ablation of metals in water during the production of nanoparticles are discussed. Three fast diagnostic methods have been applied simultaneously. These are Optical Emission Spectroscopy for the plasma characterization, fast shadowgraph for plasma and cavitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
164
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(181 citation statements)
references
References 29 publications
7
164
1
3
Order By: Relevance
“…At that moment, the plasma expansion, which firstly experienced a fast-growing stage, also becomes stable. These calculated results are consistent with the observation that the plasma reaches the maximum volume after a few hundred nanoseconds [18,23]. Wu et al [19] have also found that, for the ∼1 GW/cm 2 laser ablation, the plasma length can only expand in 1 µs after the laser peak.…”
Section: Fig 1 (And Supplementarysupporting
confidence: 79%
See 3 more Smart Citations
“…At that moment, the plasma expansion, which firstly experienced a fast-growing stage, also becomes stable. These calculated results are consistent with the observation that the plasma reaches the maximum volume after a few hundred nanoseconds [18,23]. Wu et al [19] have also found that, for the ∼1 GW/cm 2 laser ablation, the plasma length can only expand in 1 µs after the laser peak.…”
Section: Fig 1 (And Supplementarysupporting
confidence: 79%
“…First, the stable state of the plasma induced by laser ablation can be regarded as the nucleation point of the cavitation bubble. This process is theoretically modeled in the present letter, although its experimental evidence is clear [18,23]. Second, the initial evolution of the first bubble is accompanied by the target's ablation in the form of an explosive boiling [14].…”
Section: Fig 1 (And Supplementarymentioning
confidence: 99%
See 2 more Smart Citations
“…colloidal solutions have been obtained in water and organic solvents instantaneously [12][13][14]. Laser ablation in liquid is a low cost technique because it does not need vacuum equipment, not wet chemistry processes are required and the formed nanoparticles, being stored in the liquid as a colloidal dispersion, are easily collected after the synthesis.…”
Section: Introductionmentioning
confidence: 99%